SYSTEMATIC LITERATURE REVIEW OF THE BANKING SECTOR BUSINESS SUSTAINABILITY MODEL - Yusuf, Yusuf (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Technological developments and fierce competition in the banking sector demand adopting Indonesia’s suitable business continuity model. This sustainability is reflected in the financial and non-financial reports that cover environmental aspects and company conditions. The report provides information about the process of making environmentally friendly products, production that cares about the environment, using natural resources, developing efficient innovation, and transparent and credible corporate accounting. This study uses a literature review to identify models of banking business sustainability in various countries as input for banking management in Indonesia to remain sustainable. From the search results, it is concluded that the banking business sustainability model can be achieved by adopting the Green Banking business model, namely integrating environmental management and banking operations to change the financial industry and create environmentally friendly banking operations following the Millennium Development Goals (MDGs), paying attention to governance and risk management, adopting religious values, the portion of entity ownership, the role of the government in encouraging transparency through regulations that promote sustainability and the use of digitalization and website technology to make sustainability even better.